PENGARUH KEBERAGAMAN PRODUK DAN MEMBER CARD TERHADAP LOYALITAS KONSUMEN PADA TOKO CENTRAL BUSANA PANAM, PEKANBARU - Mutiyah, Kurnia; Sutrisna, Endang (Jurnal Daya Saing, 2025)
Abstract: The purpose of this study was to determine how consumer loyalty at the Panam Central Busana Store, Pekanbaru is related to product diversity and member cards. Product diversity and member cards are independent variables while consumer loyalty is the dependent variable. The problems that occurred at the Panam Central Busana Store were a decrease in the number of consumers/visitors from the previous year, failure to achieve the target realization, and the emergence of several competitors who were also engaged in the fashion retail sector around the Panam Central Busana Store which became a threat to the Panam Central Busana Store itself. The sample in this study was determined using the slovin formula obtained, namely 97 respondents. This type of research is quantitative research using questionnaire data collection techniques through gform and questionnaires. The data obtained from the results of the questionnaire distributed using purposive sampling techniques were then processed for further study with the SPSS 25 program. The results of the tests carried out showed that product diversity has an influence on consumer loyalty, where t count = 20.157> t table 1.661 and sig 0.000 <0.05, then member cards have an influence on consumer loyalty, where t count = 15.369> t table 1.661 and sig 0.000 <0.05, and product diversity and member cards on consumer loyalty, with F count 301.654> F table 3.092, and sig 0.000 <0.05. Keywords: Product Diversity, Member Card, Consumer Loyalty, Central Panam Fashion Store, Pekanbaru, Quantitative.